2018
DOI: 10.1177/0954406218813188
|View full text |Cite
|
Sign up to set email alerts
|

The effects of S-glass fiber hybridization on vibration-damping behavior of intraply woven carbon/aramid hybrid composites for different lay-up configurations

Abstract: In this study, the vibration and damping characteristics of the hybrid composites reinforced with plain woven S-glass and intraply woven carbon/Kevlar fiber fabrics are investigated. Vibration tests on the samples have been conducted only for measuring the first mode of natural frequency with application of experimental modal analysis procedures. Symmetric and asymmetric layering structures have been prepared for the hybrid composite configurations in order to study the stacking sequence effects. Damping ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In addition, first modes of natural frequency values with loss and storage modulus of the samples are given in Table 4. Results from dynamic tests suggested that increasing of the natural frequency was explained by the fact that the elastic modulus enhancement of OP particles included test samples [24]. However, increase in the elastic modulus may not meant the enhancement of the damping properties since the damping property highly depends on viscoelastic nature of the materials, revealing the better vibrational energy absorption, exhibiting high modulus of storage [25].…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…In addition, first modes of natural frequency values with loss and storage modulus of the samples are given in Table 4. Results from dynamic tests suggested that increasing of the natural frequency was explained by the fact that the elastic modulus enhancement of OP particles included test samples [24]. However, increase in the elastic modulus may not meant the enhancement of the damping properties since the damping property highly depends on viscoelastic nature of the materials, revealing the better vibrational energy absorption, exhibiting high modulus of storage [25].…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…15 It was found that the loss factor, h, obtained via the hysteresis loop method was linearly dependent only on the applied excitation frequency and was independent of the preloading and the stress amplitudes. 16 In Bulut et al, 18 the results revealed that the position and the percentage of the fibres in composites were the most effective parameters for natural-frequency and damping characteristics. Even in cutting, the amount of wooden reinforcement in wood-plastic composites affects the shape of the formed chips.…”
Section: Introductionmentioning
confidence: 98%
“…[18][19][20][21] Thus far, a number of studies have confirmed the effectiveness of this method. [22][23][24][25][26][27][28] For instance, a study conducted by Yeter et al [29] studied the hybridization effect on the buckling characteristics of various fiber-reinforced plates. They reported that the buckling characteristics of composite plates were affected by the hybridization as well as the fiber stacking sequence.…”
Section: Introductionmentioning
confidence: 99%